Clinical-Pathological Parameters as Prognostic Indicators in Oral Squamous Cell - Raimundo Fernandes de ARAÚJO JÚNIOR; Antonio de Lisboa Lopes COSTA; César Formiga RAMOS (Association of Support to Oral Health Research (APESB), 2006)
Objective: To correlate the TNM classification and histological scores of malignancy, and these parameters with the prognosis in 38 cases of squamous cell carcinoma oral. Method: The cases were selected from the files of "Dr. Luiz Antônio" Cancer Hospital, Natal, RN, Brazil. After analysis of the patients' records, the data concerning TNM classification and prognosis (in a 5-year-follow-up) were obtained. All cases were classified according to the histological malignancy grading system proposed by Bryne (1998). Results: There was correlation between histological scores of malignancy and prognosis and TNM classification with prognosis. Conclusion: It was concluded that TNM classification and histological malignancy grading are important prognostic indicators the squamous cell carcinoma oral.